Integrating Mind Map in PBL Activities on Variation to Promote Analytical Thinking Skills - Supot Seebut, Ladda Lertsri and (Journal of Community Development Research (Humanities and Social Sciences), 2016)
Analytical thinking is considered as higher order thinking and more important than that, analytical thinking is considered as the basic of all kind of thinking that has an influence in human learning and living in daily life. However because of abstract form of thinking, finding the way to move it from abstract to concrete becomes a key successful in learning design. The purpose of this study is to develop learning activities using PBL with integrating mind map as a scaffolding tool applied for supporting students to present analytical thinking skills in concrete form simultaneously with motivating it by problem solving process on Variation. To determine the effect of using learning activities based on PBL with integrating mind map on the levels of students’ analytical thinking skills, three subjective tests about subject matter on Variation are administered as posttest to student. The rubric score is employed to determine the level of students’ analytical thinking skills through their performing in subjective tests. Data from rubric for evaluating student’ analytical thinking skills is analyzed using descriptive statistics to find frequency of students identifying particular student’ skill levels in analytical thinking for each of essential features of analytical thinking skills and to compute the mean skill levels in analytical thinking of students for each essential features. The results have verified the significant effect that learning activities using PBL with integrating mind map have an effect on students’ analytical thinking skills.   Keywords: Analytical Thinking Skills, Mind Map, Problem Based Learning, Problem Solving, Variation
Keywords: Analytical Thinking Skills, Mind Map, Problem Based Learning, Problem Solving, Variation